Aplikasi Teknologi Nanopartikel Perak (AgNPs) dalam Air Minum dan Bentuk Kabut terhadap Kadar Amonia Ekskreta Broiler - O P Hulu; M Sihombing; R H Saputro; A Darmawan; Y Herbani (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
The purpose this study was evaluate the utilization of nanoparticles silver (AgNPs) on performance and ammonia concentration in broiler excreta. This study used a factorial completely randomized design with 3x2 treatments and 4 replicates. First factor (AgNPs at drinking water) was P1 = 0 ppm, P2 = 2 ppm, and P3 = 3 ppm and the second factor Q (AgNPs by misty) was Q1 = 0 ppm and Q2 = 4 ppm. The variables measured were excreta ammonia content, feed consumption, body weight gain, feed conversion ratio, mortality, temperature and relative humidity. The results showed that there was no interaction between AgNPs in drinking water and AgNPs in its mist form on ammonia content. AgNPs 4 ppm by misty also affected reduce FCR and body weight gain at week 3, also increased FCR at fourth week. AgNPs in drinking water affected (P < 0.05) amonia content. AgNPs 2 ppm in drinking water reduce until 11% amonia content. AgNPs by misty also reduced (P< 0.05) amonia content. AgNPs 0 ppm and 4 ppm by misty not created comfort temperature and relative humidity for broiler chicks. It is concluded that the addition of silver nanoparticles reduce excreta ammonia levels of broiler chickens. Key words: amonia, humidity, misty, NanoSilver Particles (AgNPs), relative temperature